2019
DOI: 10.1093/cvr/cvz009
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery plaque characteristics and treatment with biologic therapy in severe psoriasis: results from a prospective observational study

Abstract: The use of biologic therapy has increased over the past decade well beyond primary autoimmune diseases. Indeed, a recent trial using an anti-IL-1beta antibody reduced second myocardial infarction (MI) in those who have had MI. Psoriasis is a chronic inflammatory disease often treated with biologics when severe, is associated with increased risk of MI, in part driven by high-risk coronary plaque phenotypes by coronary computed tomography angiography (CCTA). We hypothesized that we would observe a reduction in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
153
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(168 citation statements)
references
References 33 publications
8
153
1
6
Order By: Relevance
“…Specifically, lengthier biologic DMARD treatment reduced the likelihood of noncalcified plaque progression, the earliest histologic atherosclerotic lesion discernible on coronary CT angiography. Biologic therapies were similarly shown to selectively influence lipid‐rich, soft plaque volume in patients with psoriasis . Moreover, we showed that lengthier biologic DMARD exposure appeared to prevent maturation and remodeling of such plaques, as evidenced by the lower risk of progressive calcification independent of inflammation, duration of statin exposure, and total prednisone dose.…”
Section: Discussionmentioning
confidence: 66%
“…Specifically, lengthier biologic DMARD treatment reduced the likelihood of noncalcified plaque progression, the earliest histologic atherosclerotic lesion discernible on coronary CT angiography. Biologic therapies were similarly shown to selectively influence lipid‐rich, soft plaque volume in patients with psoriasis . Moreover, we showed that lengthier biologic DMARD exposure appeared to prevent maturation and remodeling of such plaques, as evidenced by the lower risk of progressive calcification independent of inflammation, duration of statin exposure, and total prednisone dose.…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, psoriasis patients receiving anti-TNF treatment exhibited decreased vascular inflammation and a gender-dependent effect on carotid plaque progression after 1 year (88). Further evidence of the effect of anti-IL-17A treatment on cardiovascular disease in psoriasis was provided by Elnabawi et al (89). In this prospective observational study, 121 patients without prior systemic therapy received treatment with various biologicals for 1 year; 169 patients with topical and/or phototherapy served as controls.…”
Section: Cardiovascular Inflammation In Psoriasis Experimental and CLmentioning
confidence: 89%
“…Other studies assessed the carotid plaque burden in psoriasis patients during biologic treatment (88,89). Interestingly, psoriasis patients receiving anti-TNF treatment exhibited decreased vascular inflammation and a gender-dependent effect on carotid plaque progression after 1 year (88).…”
Section: Cardiovascular Inflammation In Psoriasis Experimental and CLmentioning
confidence: 99%
“…your Cardiovascular Research', we shared insights on how to publish high-impact science which was followed by talks discussing visibility for authors who publish in Cardiovascular Research, ethics in scientific publishing, as well as authors of top papers discussing their highly cited papers and most recent work. 42 We also encourage authors, including Young Investigator Award finalists, to submit their work to Cardiovascular Research, as we continue to remain dedicated to helping drive the development of the cardiovascular science community at the frontiers, as well as actively promoting and supporting young investigators. We anticipate and look forward to a fruitful FCVB conference in Budapest, 2021 and hope to see you all there.…”
mentioning
confidence: 99%